SURGICAL MANAGEMENT OF SUPRASELLAR GERMINOMA: INSIGHTS FROM A CRANIOTOMY CASE - Monica Halim; Andrea Valentino; Agustiawan Agustiawan (International Archives of Medical Sciences and Public Health, 2026)
Intracranial germinoma is a rare midline CNS tumor, most commonly arising in the suprasellar or pineal regions. Suprasellar lesions frequently cause hypothalamic–pituitary dysfunction, resulting in diabetes insipidus, endocrine abnormalities, and visual impairment. We report a 21-year-old man with a two-year history of progressive visual blurring and polyuria polydipsia that culminated in acute loss of consciousness. Imaging revealed a suprasellar mass, and clinical deterioration required intensive care admission. Craniotomy was performed for tumor decompression and histopathological diagnosis, confirming germinoma. Postoperative radiotherapy led to recovery of consciousness after the third session and marked tumor regression to approximately 1 cm, demonstrating the tumor’s high radiosensitivity. Despite favorable oncologic response, residual deficits persisted, including left-sided visual blurring, complete right-eye blindness, severe hypocortisolemia, and low prolactin levels requiring hormone replacement therapy. This case emphasizes the importance of early diagnosis, individualized treatment, and multidisciplinary management to achieve tumor control while addressing long term neurological and endocrine sequelae. Survivorship-focused care integrating endocrinology, rehabilitation, psychosocial support, and adherence monitoring is essential, particularly in resource-limited settings, to improve treatment continuity, reduce complications, and enhance quality of life among young brain tumor survivors.